THU0342 Utilizing "real life" data in order to evaluate the association between giant cell arteritis and autoimmune thyroid disease. (15th June 2017) - Yavne, Y; Tiosano, S; Watad, A; Comaneshter, D; Shoenfeld, Y; Cohen, AD; Amital, H
Abstract : Background: In 1977, How et al. 1 described the case of a simultaneous presentation of giant cell arteritis (GCA) and hypothyroidism. In the following decades, numerous studies have attempted to determine whether a significant interaction exists between GCA and autoimmune thyroid dysfunction, with conflicting results 2–5 . Objectives: To evaluate whether a genuine association exists between GCA and autoimmune thyroid disease. Methods: Utilizing the medical database of Clalit Health Services, we compared the proportion of autoimmune thyroid disease between patients with GCA and age- and gender-matched controls in a cross-sectional study. Univariate analysis was performed using Chi-square and student t-test and a multivariate analysis was performed using a logistic regression model. Results: 5, 663 GCA patients and 23, 308 age- and gender-matched controls were included in the study. The proportion of hypothyroidism amongst GCA patients was increased in comparison with controls (18.2% vs. 6.91%, respectively, p - value <0.001), as was hyperthyroidism (2.56% and 1.19% respectively, p - value <0.001). After controlling for confounders, GCA demonstrated a robust independent association with hypothyroidism on multivariate logistic regression (OR 1.297, 95% CI 1.187–1.418, Table 1 ). In contrast, when a similar model was performed in order to assess the nature of the association between GCA and hyperthyroidism, it was found to be non-significant, with an OR of 1.097. Conclusions: GCA patients have a higher proportion of hypothyroidism in comparison with matched controls. A significant association between GCA and hyperthyroidism was not found. Physicians treating GCA patients should consider screening for thyroid dysfunction on a regular basis. References: How J, Bewsher PD, Walker W. Giant-cell arteritis and hypothyroidism. Br Med J. 1977;2(6079):99. Wiseman P, Stewart K, Rai GS. Hypothyroidism in polymyalgia rheumatica and giant cell arteritis. BMJ. 1989;298(6674):647. Bowness P, Shotliff K, Middlemiss A, Myles AB. Prevalence of hypothyroidism in patients with polymyalgia rheumatica and giant cell arteritis. Rheumatology. 1991;30(5):349–351. Duhaut P, Bornet H, Pinède L, et al. Giant cell arteritis and thyroid dysfunction: multicentre case-control study. BMJ. 1999;318(7181):434–435. Myklebust G, Gran JT. A prospective study of 287 patients with polymyalgia rheumatica and temporal arteritis: clinical and laboratory manifestations at onset of disease and at the time of diagnosis. Rheumatology. 1996;35(11):1161–1168. Disclosure of Interest: None declared